A librarian lifestyle / Aslam Kamarudin - Kamarudin, Aslam (Faculty of Information Management, 2015)
Based on my own experience, when we talk about the librarian, some people think that working as a librarian is such a boring work which just sit and watched the users of the library doing their research starring from early in the morning and go back in the evening when the time to close the library has come. In fact, they didn't know the actual roles of the librarians that are nearby them such as reference librarians whereby they are actually ready all the time to help in guiding the user that are in need in the process of searching and retrieving information regarding their field of works.